Awareness about Normal Vaginal Delivery among Pregnant Women Attending at an Upazilla Health Complex - Zafreen, Farzana; Wahab, Md Abdul; Ahmed, Mohsen Uddin; Rahman, Md Habibur; Razzak, Md Abdur (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Childbirth is a personal and individual journey that is different for every woman. Perception of the birth experience is thought to be influenced by many factors, the most significant of which may be the type of delivery. Normal vaginal delivery (NVD) is a natural process and cesarean section (CS) an operative process for child birth. Awareness regarding mode of delivery have a very important role for the future wellbeing of mother and child both. Objectives: To assess the awareness regarding normal vaginal delivery among pregnant women attending the out patients department (OPD) of an Upazilla Health Complex. Materials and Methods: This descriptive cross-sectional study was conducted at Kaliganj Upazilla Health Complex, Gazipur from January to March 2018 among 300 pregnant women. Age range of the patients was 15-40 years and selected purposively who were willing to attend and having no major complications. Data were collected by face to face interview with structured questionnaire and analyzed by SPSS version 20.0 Results: Out of 300 respondents 103(34.3%) was within 21-25 years, 87(29%) was within 26-30 years and 61(20.3%) was below 20 years of age. Respondents’ age at marriage found 113(37.7%) was within 21-25 years and 107(35.7%) below 20 years. About 178(59.3%) was regular and 122(40.7%) was irregular about their antenatal care visit. Common health problem was weakness 185(61.7%), GDM 67(22.3%) and swelling feet 21(7%). Among 211 respondents 133(63%) was satisfied, 40(19%) was dissatisfied and 38(18%) having mixed feelings about their previous delivery. Regarding awareness about mode of delivery 207(69.3) opted NVD better, 56(18.7%) opted CS better and 30(10%) was confused. Regarding preferred mode of delivery 191(63.7%) opined for NVD, 52(17.3%) opined for CS and 57(19%) was not clear about their opinion. Conclusion: Study found that majority of respondent was aware about the NVD but still good number of participant opted CS as their choice. Proper health education and creating awareness by mass media and healthcare worker and community leader may improve the situation. Journal of Armed Forces Medical College Bangladesh Vol.15 (1) 2019: 35-38